Atomistic Investigation of Load Transfer Between DWNT Bundles "Crosslinked" by PMMA Oligomers. (6th November 2012) - Naraghi, Mohammad; Bratzel, Graham H.; Filleter, Tobin; An, Zhi; Wei, Xiaoding; Nguyen, SonBinh T.; Buehler, Markus J.; Espinosa, Horacio D.
Abstract The production of carbon nanotube (CNT) yarns possessing high strength and toughness remains a major challenge due to the intrinsically weak interactions between "bare" CNTs. To this end, nanomechanical shear experiments between functionalized bundles of CNTs are combined with multiscale simulations to reveal the mechanistic and quantitative role of nanotube surface functionalization on CNT‐CNT interactions. Notably, the in situ chemical vapor deposition (CVD) functionalization of CNT bundles by poly(methyl methacrylate) (PMMA)‐like oligomers is found to enhance the shear strength of bundle junctions by about an order of magnitude compared with "bare" van der Waals interactions between pristine CNTs. Through multiscale simulations, the enhancement of the shear strength can be attributed to an interlocking mechanism of polymer chains in the bundles, dominated by van der Waals interactions, and stretching and alignment of chains during shearing. Unlike covalent bonds, such synergistic weak interactions can re‐form upon failure, resulting in strong, yet robust fibers. This work establishes the significance of engineered weak interactions with appropriate structural distribution to design CNT yarns with high strength and toughness, similar to the design paradigm found in many biological materials.